2022
DOI: 10.1002/ange.202201004
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Syngas to Higher Alcohols via Tandem Integration of Fischer–Tropsch Synthesis and Reductive Hydroformylation

Abstract: The selective conversion of syngas to higher alcohols is an attractive albeit elusive route in the quest for effective production of chemicals from alternative carbon resources. We report the tandem integration of solid cobalt Fischer-Tropsch and molecular hydroformylation catalysts in a one-pot slurry-phase process. Unprecedented selectivities (> 50 wt %) to C 2 + alcohols are achieved at CO conversion levels > 70 %, alongside negligible CO 2 side-production. The efficient overall transformation is enabled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…According to the number of metal types involved in the active phase, HAS catalysts can be briefly classified into monometallic and bimetallic active sites. Herein, we mainly discuss the significant advances in monometallic and bimetallic active sites as well as emerging multifunctional catalytic systems. Typical catalytic performances over various typical active sites are summarized in Table S3.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…According to the number of metal types involved in the active phase, HAS catalysts can be briefly classified into monometallic and bimetallic active sites. Herein, we mainly discuss the significant advances in monometallic and bimetallic active sites as well as emerging multifunctional catalytic systems. Typical catalytic performances over various typical active sites are summarized in Table S3.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…Another type of multifunctional catalyst is composed of a modified FTS component and an olefin hydroformylation component via tandem catalysis. , The key idea is to transform the coproduced olefins into oxygenates, thus enhancing the total selectivity of HA products. Li et al reported a tandem catalyst composed of activated carbon-supported CoMn and Rh-metalated 3v-PPh 3 -based porous organic polymers (CoMn/MAC|Rh/3v-PPh 3 @POPs) that exhibited excellent oxygenate selectivity (62.7%) with the percentage of C 2+ OH and C 6+ OH over 96.6% and 70.7%, respectively .…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
See 3 more Smart Citations